Geo Routing Based Algorithm Investigation to Track Website Quality Using Geo-Location - Chandran, M (International Journal of Computer Sciences and Engineering, 2018)
The study of the research is to collect the information like users browsing place, browser used, IP Address, latitude, longitude and operating system automatically when the time of client browsing. With the help of geocast, Geo-Location and the collected information, it will map the client browsed position in the Google Map. This is a web based research used to track all kind of website information in any specific platform. This system collects a large number of users’ browsing information to analyze the website performance, load balancing, web traffic and finding errors for taking the essential improvements. This research is also to find the shortest path from the client browsing place to website hosted server. It will reach the specific routers to find the shortest path. Each and every router will have the router name and IP Address. It collects the router information by using tracert command and shows the geographic location in the Google Map. It shows the various kinds of information’s like, Client captured IP Address, Routers location and IP Address, Total hits of the website right from the beginning, Country based website hits, Region based website hits, City based website hits, Browser based website hits and Platform based website hits. Each and every information, there is a graph for easy identification.